Discipline and Institution Commitment: Professorial Views - Glaz-Fontes, Jesús (International Higher Education, 2010)
Amid increasing expectations for socioeconomic relevance, higher education confronts, in many countries, a similar set of challenges: declining general-support levels linked with more performance-based funding, expanded enrollment demand, an increasingly knowledge-based and global economy, and a more intense managerialism. While giving unprecedented centrality to academic work, deteriorating conditions of work and of increased accountability has placed more performance pressure on the faculty.